Dynamics of volatile organic compounds in a western Mediterranean oak forest. (15th July 2021) - Yáñez-Serrano, Ana Maria; Bach, Albert; Bartolomé-Català, David; Matthaios, Vasileios; Seco, Roger; Llusià, Joan; Filella, Iolanda; Peñuelas, Josep
Abstract: Volatile organic compounds (VOCs) are emitted from many sources and have important implications for plant fitness, ecological interactions, and atmospheric processes, including photochemistry and ozone formation. Forest ecosystems are strong sources of biogenic VOCs. We aimed to characterize forest below-canopy VOC mixing ratios, monitored by Proton Transfer Reaction Mass Spectrometry (PTR-MS), at Montseny Natural Park, a Mediterranean forest 50 km from the Barcelona urban area. Measurements were taken every 2 min during six months around the maximum emission period of summer. All VOCs had diel cycles with higher mixing ratios during the day, but different patterns over time. Monitored VOCs were grouped as biogenic, oxygenated, or aromatic compounds. Additionally, a positive matrix factorization analysis identified four emission profiles that were attributed to photochemical VOC production, biogenic emissions, mixed VOC emission sources, and traffic emissions. Even though the biogenic source was the strongest source profile at the site, we found a strong influence of anthropogenic air masses infiltrating the forest canopy and altering the biogenic air masses at the site. Graphical abstract: Image 1 Highlights: We analysed the below canopy volatile organic compounds of a Mediterranean forest of the Iberian Peninsula for six months. Biogenic VOC emissions dominated at the forest, but there was strong influence from anthropogenic sources from elsewhere. We identified photochemical VOC production, biogenic, mixed VOC, and traffic emissions sources. We show how the atmospheres of forested ecosystems could be substantially affected by anthropogenic VOC sources.